Relationship between capacitance values and diesel contamination levels in crude palm oil - Chin @ Hashim, Nur Fizura; Abd Aziz, Samsuzana; Saringat, Hafizan (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Measurement of crude palm oil (CPO) contamination is a major concern in CPO quality monitoring. In this study, capacitive sensing technique was used to measure diesel contamination levels in CPO. This technique was choosing because it is provide immediately real-time information of contamination in CPO. Low cost capacitive sensing system was developed in this study by using AD7746 capacitance to digital converter. The effect of diesel contamination levels range from 0% to 50% in CPO and the output of capacitance sensor at a room temperature (25°C) were investigated. The results showed that capacitance value decreased with increases in diesel contamination levels. The regression model for this research y=0.0002x2-0.0125x+0.9360 with r2 value of 0.96. These results indicated that capacitive sensing technique has potential for CPO quality monitoring.